Imaging modalities for the classification of gout: systematic literature review and meta-analysis. Issue 10 (10th June 2014) - Ogdie, Alexis; Taylor, William J; Weatherall, Mark; Fransen, Jaap; Jansen, Tim L; Neogi, Tuhina; Schumacher, H Ralph; Dalbeth, Nicola
Abstract : Background: Although there has been major progress in gout imaging, no gout classification criteria currently include advanced imaging techniques. Objective: To examine the usefulness of imaging modalities in the classification of gout when compared to monosodium urate (MSU) crystal confirmation as the gold standard, in order to inform development of new gout classification criteria. Methods: We systematically reviewed the published literature concerning the diagnostic performance of plain film radiography, MRI, ultrasound (US), conventional CT and dual energy CT (DECT). Only studies with MSU crystal confirmation as the gold standard were included. When more than one study examined the same imaging feature, the data were pooled and summary test characteristics were calculated. Results: 11 studies (9 manuscripts and 2 meeting abstracts) satisfied the inclusion criteria. All were set in secondary care, with mean gout disease duration of at least 7 years. Three features were examined in more than one study: the double contour sign (DCS) on US, tophus on US, and MSU crystal deposition on DECT. The pooled (95% CI) sensitivity and specificity of US DCS were 0.83 (0.72 to 0.91) and 0.76 (0.68 to 0.83), respectively; of US tophus, were 0.65 (0.34 to 0.87) and 0.80 (0.38 to 0.96), respectively; and of DECT, were 0.87 (0.79 to 0.93) and 0.84 (0.75 to 0.90), respectively. Conclusions: US and DECT show promise for gout classification but the few studies to date have mostly been in patients with longstanding, established disease. The contribution of imaging over clinical features for gout classification criteria requires further examination.